Research on the Development Evaluation Method of TOD Development of Metro Station Domain - Zheng, Tiantian; Bian, Yang; Li, Lixuan; Zhang, Xiaodong (Transactions on Economics, Business and Management Research, 2024)
The public transport-oriented TOD model is a sustainable planning concept currently being implemented. It’s in the TOD area. Most destinations can be reached directly by public transport. This emphasizes the attractiveness of public transport for residents to travel and reduces people’s over-reliance on private cars, thereby improving urban problems such as diseases and traffic congestion in big cities. However, at present, the evaluation methods of TOD development effectiveness at home and abroad are insufficient in pertinence and timeliness, and can not fully evaluate the development effectiveness of TOD in orbital station area. This article takes the Beijing Metro Railway Station as an example to carry out the effective evaluation method of TOD development in the rail station domain. This paper tries to put forward a set of practical and effective evaluation methods for the development of orbital station TOD in Beijing. Therefore, it provides technical support for the further promotion of TOD development mode in the process of new city planning and old city renewal in Beijing.